Complementary feeding intervention on stunted Guatemalan children: a randomised controlled trial. Issue 1 (27th April 2018) - Martinez, Boris; Webb, Meghan Farley; Gonzalez, Ana; Douglas, Kate; Grazioso, Maria del Pilar; Rohloff, Peter
Abstract : Objective/background: Guatemala's indigenous Maya population has one of the highest rates of childhood stunting in the world. The goal of this study was to examine the impact of an intensive, individualised approach to complementary feeding education for caregivers on feeding practices and growth over usual care. Design: An individually randomised (1:1 allocation ratio), parallel-group superiority trial, with blinding of study staff collecting outcome data. Setting: Rural Maya communities in Guatemala. Participants: 324 children aged 6–24 months with a height-for-age Z score of less than or equal to −2.5 SD were randomised, 161 to the intervention and 163 to usual care. Interventions: Community health workers conducted home visits for 6 months, providing usual care or usual care plus individualised caregiver education. Main outcomes measures: The main outcome was change in length/height-for-age Z score. Secondary outcomes were changes in complementary feeding indicators. Results: Data were analysed for 296 subjects (intervention 145, usual care 151). There was a non-significant trend to improved growth in the intervention arm (length/height-for-age Z score change difference 0.07(95% CI −0.04 to 0.18)). The intervention led to a 22% improvement in minimum dietary diversity (RR 1.22, 95% CI 1.11 to 1.35) and a 23% improvement in minimal acceptable diet (RR 1.23, 95% CI 1.08 to 1.40) over usual care. Conclusions: Complementary feeding outcomes improved in the intervention arm, and a non-significant trend towards improved linear growth was observed. Community health workers in a low-resource rural environment can implement individualised caregiver complementary feeding education with significant improvements in child dietary quality over standard approaches. Clinical trial registration number: NCT02509936 . Stage: Results